The risk of malnutrition as a predictor of arrhythmia recurrence after catheter ablation in patients with paroxysmal non-valvular atrial Fibrillation and heart failure with preserved ejection fraction - Zixi Zhang; Cancan Wang; Qiming Liu; Yichao Xiao; Jiabao Zhou; Keke Wu; Yunying Huang; Zeying Zhang; Shiping Liu; Qiuzhen Lin (PLoS ONE, 2025)
Background Malnutrition presents a significant challenge in managing patients with atrial fibrillation (AF) and heart failure with preserved ejection fraction (HFpEF), yet its impact on AF recurrence after catheter ablation in this population remains unclear. Methods We conducted a retrospective analysis of 204 patients with paroxysmal non-valvular AF and HFpEF who underwent radiofrequency or cryoballoon ablation. Risk of malnutrition as assessed using three screening tools: the Controlling Nutritional Status (CONUT) score, Prognostic Nutritional Index (PNI), and Nutritional Risk Index (NRI)]. We examined the relationship between risk of malnutrition and AF recurrence post-ablation. Results After a mean follow-up period of 11.2 ±  1.8 months, 43 patients (21.1%) experienced AF recurrence. Despite being classified as overweight or obese based on body mass index, many patients were at risk of malnutrition according to the CONUT score, NRI, and PNI. Adjusted analyses showed that higher CONUT scores (HR: 10.132; 95% CI: 2.545–40.336; P =  0.001), lower NRI (HR: 22.734; 95% CI: 6.399–80.776; P <  0.001), or lower PNI (HR: 9.469; 95% CI: 3.232–27.739; P <  0.001) were significantly associated with increased risk of AF recurrence. Restricted cubic spline regression revealed an inverted U-shaped relationship between the CONUT score and AF recurrence, and L-shaped relationships for both NRI and PNI with AF recurrence. Conclusions Systematic nutritional assessment is crucial in patients with paroxysmal non-valvular AF and HFpEF. High CONUT scores, low NRI, or low PNI serve as independent predictors for AF recurrence. Further large-scale randomized controlled trials are required to validate these findings.